Interrelationships among health, environment quality, and economic activity: What consequences for economic convergence? - Alassane Drabo (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2011)
This paper examines the link between health indicators, environmental variables, and economic development, and the consequences of this relationship on economic convergence. In the early stage of economic development, the gain from income growth could be cancelled or mitigated by environmental degradation through health (and other channels), and create a vicious circle in economic activity unlike in developed countries. This in turn could slow down economic convergence. We found through an econometric analysis that environmental degradation affects economic activity negatively and reduces the ability of poor countries to reach developed ones economically.
Keywords: C33; I18; O11; O40; Q5; 330; environmental quality; health indicator; income growth; economic convergence; speed of convergence